Real-world laboratories as an approach for reducing plastic outflow into the North Sea: A case study on opportunities and risks in design and implementation in Northwest Germany - Heisel-Sure, Yannik; Kemmner, Gisela; Tebelmann, Hana; Krebs, Antonia (ERDKUNDE, 2025)
Global plastics production has grown rapidly in recent decades and is leading to an increased discharge of plastic waste into the environment, presenting a complex socio-ecological problem. The southern North Sea and its tributaries are affected by plastic pollution due to dense population, industrial use, as well as tourism and recreational activities. A paradigm shift is necessary to reduce the outflow of plastic waste from rivers and inland waters into the North Sea. In order to foster a socio-ecological transformation, one opportunity is to involve stakeholders from all sectors, who regulate, produce, trade, use, recycle and dispose plastic products, through a transdisciplinary process. Real-world laboratories as a science-practice interaction approach are conceptualised to produce robust knowledge to solve real-world environmental and societal challenges. The aim of this study is to determine how the design and early implementation phases of real-world laboratories should be executed to achieve socio-ecological transformation. We assessed the case study of an inaugural regional stakeholder meeting of the real-world laboratory ‘Plastic-FREE-sia’ in Northwest Germany by in-event observations and a subsequent participant survey. Our findings of this stakeholder workshop highlight the significance of involving diverse stakeholders from multiple sectors in the real-world laboratory process and emphasise the need for balanced representation. The interests, benefits and goals of individual stakeholders must be identified from the outset and aligned with the socio-ecological problem setting, in order to prevent conflicting objectives. Concluding recommendations for the design and early implementation phases of future real-world laboratories are formulated.